Usage and effectiveness of systemic treatments in adults with severe atopic eczema: First results of the German Atopic Eczema Registry TREATgermany. (10th November 2016) - Schmitt, Jochen; Abraham, Susanne; Trautmann, Freya; Stephan, Victoria; Fölster‐Holst, Regina; Homey, Bernhard; Bieber, Thomas; Novak, Natalija; Sticherling, Michael; Augustin, Matthias; Kleinheinz, Andreas; Elsner, Peter; et al.
Summary: Background: The goal of clinical registries is to document the use and effectiveness of therapeutic interventions under real‐life conditions. They are an indispensable prerequisite of evidence‐based health care. Methods: Initiated in 2011, the German Atopic Dermatitis Registry TREATgermany is the first registry of patients with severe atopic dermatitis worldwide. Adults with severe atopic dermatitis (current/prior systemic antiinflammatory treatment and/or objective SCORAD ≥ 40) are prospectively followed over the course of 24 months. Employed treatment modalities are documented, and validated measuring tools are used to assess clinical disease severity (EASI, objective SCORAD), quality of life (DLQI), symptoms (POEM), global disease severity, as well as patient satisfaction. Herein, we describe the characteristics, therapeutic selection, and effectiveness of systemic antiinflammatory treatments of patients enrolled in the registry until October 2014. Results: Overall, 78 individuals (mean age 39 years, 61 % men) were enrolled at five recruitment centers. Patients frequently made use of inpatient and outpatient services. Not only was cyclosporine the most frequently administered systemic treatment, but also the most effective (EASI 50 response rate 51 %; EASI 75 response rate 34 % at 12 weeks). Azathioprine, methotrexate, oral prednisolone, mycophenolate, alitretinoin, and leflunomide were also used in some patients. Conclusions: The present analysis of the German Atopic Dermatitis Registry provides important data with respect to current medical care of adults with severe atopic dermatitis in Germany. It shows the high disease burden, the benefits of current treatment options, and the need for additional effective and safe long‐term treatment options.